Dealloying induced N-doping in spindle-like porous rutile TiO2 for enhanced visible light photocatalytic activity. (June 2018) - Zhao, Zhengfeng; Kou, Tianyi; Zhang, Lanxiang; Zhai, Sicheng; Wang, Wen; Wang, Yan
Graphical abstract: N-doped rutile TiO2 spindles with large specific area can be successfully fabricated by a simple dealloying strategy, and exhibit excellent visible light photocatalytic activity. Highlights: N-doped rutile TiO2 with specific area of ∼167 m 2 /g was fabricated by dealloying. N-doped TiO2 shows excellent photocatalytic activity towards degradation of MO. The enhanced photocatalytic activity is caused by N doping and large surface area. Abstract: We designed a high-yield and low temperature N-doping strategy in modifying TiO2 band structure. A nanostructured porous TiO2 was obtained through dealloying of Cu80 Ti20 precursor through leaching by HNO3 . It was confirmed that nitrogen was interstitially doped into TiO2 during dealloying. The doped nitrogen greatly narrows the band gap, resulting in a wider photoresponse region. The microporous structure with large specific surface area (167.04 m 2 g −1 ) and narrowed band gap (2.61 eV) together contribute to the excellent photocatalytic activity towards degradation of methyl orange under visible light irradiation. Our work offers a novel strategy for synthesizing highly active N-doped TiO2 .